2011
DOI: 10.7124/bc.00012c
|View full text |Cite
|
Sign up to set email alerts
|

Region-specific nitric oxide production in cytosolic and mitochondrial compartments of the rat brain tissues following chronic stress-induced depression-like behavior

Abstract: Aim. To study subcellular nitrergic response in the rat brain regions following chronic stress-induced depression-like behavior. Methods. An animal model of depression induced by chronic circadian stress (CCS) established in our laboratory was used. The L-arginine, L-citrulline and reactive nitrogen species (RNS) levels were determined spectrophotometrically. Results. Immediately after CCS and four days later, a depression-like behavior of rats was observed and accompanied by a substantial persistent elevation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Results confirmed that in both EPS and Pl-OGT mice, hypothalamic mitochondria function was significantly reduced, linking placental OGT again to EPS brain programming. Hypothalamic mitochondrial dysfunction has previously been associated with altered whole-body growth and energy homeostasis, as well as stress-related depressive-like behaviors (33)(34)(35)(36)(37)(38). Therefore, the observed phenotypes in male EPS and Pl-OGT mice (HPA hyperresponsivity and dysregulated energy homeostasis) appear to be, at least in part, the result of mitochondrial dysfunction programmed by a reduction in placental OGT during gestation.…”
Section: Discussionmentioning
confidence: 98%
“…Results confirmed that in both EPS and Pl-OGT mice, hypothalamic mitochondria function was significantly reduced, linking placental OGT again to EPS brain programming. Hypothalamic mitochondrial dysfunction has previously been associated with altered whole-body growth and energy homeostasis, as well as stress-related depressive-like behaviors (33)(34)(35)(36)(37)(38). Therefore, the observed phenotypes in male EPS and Pl-OGT mice (HPA hyperresponsivity and dysregulated energy homeostasis) appear to be, at least in part, the result of mitochondrial dysfunction programmed by a reduction in placental OGT during gestation.…”
Section: Discussionmentioning
confidence: 98%